Identification of Fungal Communities in "Agarwood' from wild Aquilaria malaccensis using rDNA Spacer Sequences - Mohamed, Rozi; Phai, Lee Jong; Zali, Mohammed Syazwan; Husin, Halimah (2009)
Aquilaria malaccensis is a medium-sized tropical tree from the family Thymelaeaceae, and is the main 'agarwood' producer in Peninsular Malaysia. 'Agarwood' is a valuable fragrant resin, produced in the tree trunks of A. ma/accensis, often associated to pathological infections by fungi. In our attempt to understand the roles of fungi in 'agarwood' production, we isolated fungi from 'agarwood', collected from a wild A. ma/accensis population in Peninsular Malaysia. The fungal isolates were from the genera Fusarium, Trichoderma, Curvularia and Cunninghamella (order Mucorales) based on culture characteristics on agar medium. To confirm the genera, we analyzed genomic DNA from pure cultures and wood samples from which they were first isolated., ' Using universal primers in PCR, we amplified the intemal transcribed spacer (ITS) within the ribosomal DNA (rONA) regions. Spacer sequences provided supporting evidence to the genera designation via the culture-based method. The method promised a rapid detection and identification of fungal communities directly from environmental and wood samples.